2017
DOI: 10.1177/0163443717737611
|View full text |Cite
|
Sign up to set email alerts
|

Home on the move: negotiating differential domesticity in family life at a distance

Abstract: This article examines the ways in which 21 Overseas Filipino Workers (OFWs) in Melbourne, Australia, and their left-behind family members in the Philippines use mobile media to re-stage, experience and negotiate home. Based on deploying in-depth interviews and visual methods, the findings show the reconstruction of a sense of dwelling through mobile devices. This transformation is shaped by the performance of ritualistic practices, gender roles and socioeconomic conditions. The study also uncovers how mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…Before the COVID physical distancing restrictions, many Australian households were already using mobile devices such as smartphones and tablet computers to coordinate with family members in the home as well as maintain connections with friends and family living further away (Baldassar, 2014(Baldassar, , 2016Baldassar and Wilding, 2014;Cabalquinto, 2017;Hjorth et al, 2015Hjorth et al, , 2018Holloway et al, 2014;Zhao, 2019). For example, bringing together the literatures on the digitised home environment with that on transnational communication, Cabalquinto's (2017) study of the digital practices of Filipino workers in Melbourne showed how the concept and space of 'home' were negotiated in and by these activities. He identifies the sociospatial and temporal dimensions of these practices of home, positioning the home as a dynamic assemblage of habituated practices conducted largely with and through the messaging and video conferencing apps used on the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Before the COVID physical distancing restrictions, many Australian households were already using mobile devices such as smartphones and tablet computers to coordinate with family members in the home as well as maintain connections with friends and family living further away (Baldassar, 2014(Baldassar, , 2016Baldassar and Wilding, 2014;Cabalquinto, 2017;Hjorth et al, 2015Hjorth et al, , 2018Holloway et al, 2014;Zhao, 2019). For example, bringing together the literatures on the digitised home environment with that on transnational communication, Cabalquinto's (2017) study of the digital practices of Filipino workers in Melbourne showed how the concept and space of 'home' were negotiated in and by these activities. He identifies the sociospatial and temporal dimensions of these practices of home, positioning the home as a dynamic assemblage of habituated practices conducted largely with and through the messaging and video conferencing apps used on the devices.…”
Section: Introductionmentioning
confidence: 99%
“…They frequently connect using various social media modes such as audio and audiovisual calls, and share media and messages in individual and family group chats (e.g., Bacigalupe and Bräuninger, 2017;Neustaedter et al, 2015). These rituals are not considered substitutes for face-to-face interaction, but for families with limited opportunities to see each other, they help maintain the family identity and relationships (e.g., Cabalquinto, 2018a;Ohashi et al, 2017). While patterned routines can be fulfilling, they require an ongoing time commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Both time zone differences and poor broadband connectivity frequently pose challenges to use of synchronous media such as video calls (Gordano Peile and Ros Hijar, 2016;Ryan et al, 2015;Sandel, 2014). Digital inequality can be evident in restricted access to social media applications by governments, or when the low socioeconomic status of the left-behind family means technology is unaffordable (Cabalquinto, 2018a;Shaker, 2018). Some degree of SOCIAL MEDIA, RITUALS, AND FAMILIES 7 digital literacy is necessary for the comfortable use of social media and without this knowledge, individuals can be left behind (Smith et al, 2012).…”
Section: Asynchronous Nature Of Chat Useful For Bond Maintenance and mentioning
confidence: 99%
See 2 more Smart Citations